TaqMan qPCR for Quantification of Clonostachys rosea Used as a Biological Control Agent Against Fusarium graminearum - Gimeno, Alejandro; Sohlberg, Elina; Pakula, Tiina; Limnell, Jenni; Keller, Beat; Laitila, Arja; Vogelgsang, Susanne (Frontiers in Microbiology, 2019)
Clonostachys rosea is a biological control agent against Fusarium graminearum in small grain cereals and maize. Infections with F. graminearum do not only reduce the yield but, due to the production of mycotoxins, also affect the entire value chain of food and feed. In addition, production of other secondary metabolites such as hydrophobins, also known as gushing inducers, may cause quality challenges for the malting and brewing industry. Sustainable disease control strategies using C. rosea are treatment of infected residues of the previous crop, direct treatment of the actual cereal crop or even post-harvest treatment during malting processes. Follow-up of growth and survival of biocontrol organisms during these different stages is of crucial importance. In the current study, we developed a quantitative real-time PCR detection method that amends the currently available culture-dependent techniques by using TaqMan chemistry with a highly specific primer and probe set, targeting the actin gene. We established a sensitive assay that detects the biological control agent down to 100 genome copies per reaction, with PCR efficiencies between 90 and 100%. The specificity of the assay was confirmed against a panel of 30 fungal and 3 bacterial species including 12 members of the Fusarium head blight complex and DNA of barley, maize and wheat. The DNA of C. rosea was detected in Fusarium-infected maize crop residues that were either treated in the laboratory or in the field with C. rosea and followed its DNA throughout the barley malting process to estimate its growth during grain germination. We used a standardized DNA extraction protocol and showed that C. rosea can be quantified in different sample matrices. The availability of this method will enable the monitoring of C. rosea during experiments studying the biological control of F. graminearum on cereal crop residues and on cereal grains and will thus contribute to the development of a new disease control strategy.